The effect of non-quantal acetylcholine release on quantal miniature currents at mouse diaphragm. - Giniatullin, R A (1993)
1. The amplitude and exponential decay time constant of miniature endplate currents (MEPCs) were measured in mouse diaphragms treated with anti-cholinesterase under conditions known to modulate non-quantal acetylcholine (ACh) release. 2. Anti-cholinesterase prolonged MEPC decay and the extent of this initial prolongation was not influenced by non-quantal release. When non-quantal release was present, the decays of MEPCs became increasingly faster over several hours. This increased decay did not occur in the absence of non-quantal release. 3. Potentiation of the non-quantal release by zero Mg2+ and 1 x 10(-5) M choline, on the other hand, led to acceleration of MEPC shortening. 4. Increase of temperature from 15 to 26 degrees C and the presence of the desensitization-promoting drug proadifen (5 x 10(-6) M) accelerated the rate of MEPC shortening. 5. These observations are consistent with increased receptor desensitization due to non-quantal release. Repetitive binding of ACh to postsynaptic receptors which prolongs the time course of MEPC in anti-cholinesterase-treated endplates leads to progressive desensitization in the presence of non-quantal release and to the subsequent shortening of the quantal responses.